2020
DOI: 10.1002/acr2.11176
|View full text |Cite
|
Sign up to set email alerts
|

TSG‐6 Is Weakly Chondroprotective in Murine OA but Does not Account for FGF2‐Mediated Joint Protection

Abstract: Objective. Tumor necrosis factor α-stimulated gene 6 (TSG-6) is an anti-inflammatory protein highly expressed in osteoarthritis (OA), but its influence on the course of OA is unknown. Methods. Cartilage injury was assessed by murine hip avulsion or by recutting rested explants. Forty-two previously validated injury genes were quantified by real-time polymerase chain reaction in whole joints following destabilization of the medial meniscus (DMM) (6 hours and 7 days). Joint pathology was assessed at 8 and 12 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…However, our pellet culture and explant studies indicate that TSG-6 inhibits aggrecanse production and activity in experimental settings with high levels of inflammatory cytokines. This is consistent with a recent study showing that deletion of the Tsg6 gene in mice is associated with the rapid upregulation of proinflammatory and catabolic gene expression ( Adamts5, Ccl2 and Il1a ) following joint destabilisation[38]. Moreover, in human cartilage the level of ADAMTS5 protein is, in part, dictated by its residence time in the tissue, which is dependent on LRP-1-mediated endocytosis by chondrocytes[34]; in OA, uptake of ADAMTS5 is impaired via cytokine-dependent shedding of LRP-1 leading to increased aggrecanase activity[35].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, our pellet culture and explant studies indicate that TSG-6 inhibits aggrecanse production and activity in experimental settings with high levels of inflammatory cytokines. This is consistent with a recent study showing that deletion of the Tsg6 gene in mice is associated with the rapid upregulation of proinflammatory and catabolic gene expression ( Adamts5, Ccl2 and Il1a ) following joint destabilisation[38]. Moreover, in human cartilage the level of ADAMTS5 protein is, in part, dictated by its residence time in the tissue, which is dependent on LRP-1-mediated endocytosis by chondrocytes[34]; in OA, uptake of ADAMTS5 is impaired via cytokine-dependent shedding of LRP-1 leading to increased aggrecanase activity[35].…”
Section: Discussionsupporting
confidence: 93%
“…Here we have shown that TSG-6 acts through a novel chondroprotective mechanism, suppressing inflammatory cytokine-mediated expression of the major aggrecanase and collagenase enzymes implicated in OA pathology. Thus, our observation that TSG-6 protein is largely associated with the most damaged regions of articular cartilage is consistent with it having an intrinsic function in tissue protection rather than driving the OA disease process [30,38]. Moreover, this aligns with a wealth of data on the reparative and anti-inflammatory effects of TSG-6 in a diverse range of animal models [22].…”
Section: Discussionsupporting
confidence: 83%
“…Whole knee joints were harvested as previously described, [32][33][34] and then homogenized using an adapted stainless steel mortar in liquid nitrogen. Tissue was lysed and protein quantified by Bradford method.…”
Section: Western Blottingmentioning
confidence: 99%
“…In addition, TSG-6 affects mineralization-related diseases. The anti-inflammatory activity of TSG-6 is thought to underlie its cartilage-protective effects in rheumatoid arthritis (RA) models, and the application of TSG-6 protein or its overexpression significantly attenuates joint damage in RA models [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%